Aspects of plant dispersal in the southwestern Cape with particular reference to the roles of birds as dispersal agents - Knight, Richard Spencer; Knight, Richard Spencer (Percy FitzPatrick Institute of African Ornithology, 2017)
The dispersal of plants with particular attention to the roles birds play as dispersal agents was studied in the southwestern Cape, South Africa from 1983 to 1985. The research was organized as ten inter-related studies, each with an independent data base. Each chapter focused on a different scale of plant dispersal processes ranging from regional assemblages of plant species to individual species. At the largest scale, the seven vegetation types commonly occurring in the southwestern Cape were examined for incidence of vertebrate-dispersed plants. Coastal Thicket and Afromontane Forest were found to be the richest in these species. The colonization of vertebrate-dispersed plants was examined in an artificially cleared area of Mountain Fynbos vegetation. Enhanced densities of vertebrate-dispersed species were found in areas where perches had been provided. The seasonal availability of vertebrate-dispersed species was found to be most continuous in Coastal Thicket vegetation. Fruit displays of vertebrate-dispersed indigenous plants were found to vary from those that were sporadic and inconspicuous, to those that were conspicuous and predictable, whereas those of alien plants were usually large and conspicuous. Avian use of these fleshy fruits in Coastal Thicket was examined and found to be proportional to their availability. A study of fruit presentation in relation to leaf number and stem thickness suggested that sessile, stem attached fruits have fewer local leaves at time of ripening than fruits which are presented in panicles. This may enhance accessibility and conspicuousness of stem attached fruits for dispersal by birds. Four autecological studies tested certain predictions arising from models developed to describe fruit/frugivore interactions. The dispersal of the alien Acacia cyclops seeds by the indigenous Black Korhaan Eupodotis afra suggested that successful fruit/frugivore relationships are not necessarily the product of reciprocal evolution. The study on Chrysanthemoides monilifera found that efficient dispersal systems are not limited to plants producing small quantities of lipid-rich fruits and to dispersal by obligate frugivores. The abiotic dispersal of Quercus robur was found to be efficient in relation to vertebrate-dispersal. The study on Protasparagus aethiopicus found that the morphology of fleshy fruits may also reflect attempts to overcome the effects of non-dispersing seed predators. 1It is concluded that a gradient from a predictable to unpredictable fruit availability provides a better basis for studying fruit/frugivore interactions than the coevolutionary models. previously presented.